Giant Intrapericardial Myxoma Adjacent to the Left Main Coronary Artery - Rudziński, Piotr Nikodem; Lubiszewska, Barbara; Różański, Jacek; Michałowska, Ilona; Kruk, Mariusz; Kepka, Cezary; Kryczka, Karolina; Kurowski, Andrzej; Grajkowska, Wieslawa; Pronicki, Maciej; Demkow, Marcin (Frontiers in Oncology, 2018)
A 62-year-old woman was admitted to the hospital because of chronic cough, expectoration of thick mucus, hoarseness and tightness in the precordial area. Computed Tomography (CT) examination revealed the presence of a giant intrapericardial tumor with the dimensions of 80x38x32mm. It was located anteriorly and laterally to the left atrium, posteriorly to the pulmonary trunk and the ascending aorta. This hypodense change modeled the left atrium without evidence of invasion. CT coronary angiography and 3-dimensional reconstruction were applied to enable precise planning of cardiac surgery. CT evaluation confirmed that it is possible to remove the tumor without damage to the adjacent left main coronary artery. The patient underwent cardiac surgery with sternotomy and cardiopulmonary bypass. A cohesive, smooth, vascularized tumor pedunculated to the left atrial epicardium was visualized. The location and dimensions corresponded to those determined by CT scan examination. The entire tumor was successfully dissected together with adjacent adipose and fibrous tissue. Histological evaluation revealed the presence of myxoid cells, blood vessels, degenerative changes and microcalcifications embedded in profuse hyalinized stroma. Those histological features enabled identification of the intrapericardial tumor as a myxoma. Follow-up CT examination did not demonstrate any signs of recurrence of the myxoma. According to our knowledge, a myxoma located inside the pericardial sac has never been described before.